Meningkatkan Aktifitas Belajar Siswa dalam PembelajaranIPA dengan Metode Contextual Teaching and LearningBerbasis Produk Daur Ulang - ansori, miksan (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Indispensable a creative, innovative and contextual learning with environment, such as Contextual Teaching and Learning (CTL). CTL can utilize a variety of media as well as capable take adventage of object aroud, including replaced second-hand object in the environtment. So the contextuality of science learning can be manifestly evident in the presence of a close relationship between learning materials and things that students often encounter in real life. The purpose of the study is to find out whether the method CTL can increase activity and student learning outcome in science learning. The result is the implementatiion of CTL based recycled product can increase student activity and student learning outcome in science learning.The resul of this study also provide implication for learning process improvements by optimizing contextual learning based product. Integration of CTL with recycled products should be applied in order to enhance the realization of awareness of the surrounding environtment. Students should not stuffed with learning materials that are theoritical and far from reality. But it gives them accesible and compatiblematerial with their own need and appropiate with their daily lives.